An Application of Process Capability Indices in Swimming Teaching: 製程能力指標在游泳敎學的應用 - SU , Jung Chi; CHEN, Kuen Suan; LAI, Su Lin (Asian Journal of Physical Education & Recreation, 2002)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. Process Capability Index was an effective and convenient instrument to measure process capability and achievement. Based on the process capability indices, the researchers attempted to apply such index in teaching of swimming. After several corrections, the Swimming Teaching Index SN1 = U-M / (M-F0.315)/3, and the Swimming Teaching Gathering Effect Index = P x L were developed. Moreover, five swimming coaches in Taichung area were studied to verify the validity and reliability of the index. 製程能力指標是衡量製程能力與績效的有效且方便的工具，許多統計學家和品質工程師投入了製程能力指標的研究，使其能準確的衡量出製程能力與績效。本文即是以製程能力指標為基礎經適度修正成敎會游泳指標SN1 = U-M / (M-F0.315)/3，並據以發展游泳敎學總績效指標 = P x L，最後以台灣的台中市一處游泳池的五位游泳敎練為例，探討驗証本文所發展的指標。